2013
DOI: 10.1093/brain/awt095
|View full text |Cite
|
Sign up to set email alerts
|

Beta-propeller protein-associated neurodegeneration: a new X-linked dominant disorder with brain iron accumulation

Abstract: Neurodegenerative disorders with high iron in the basal ganglia encompass an expanding collection of single gene disorders collectively known as neurodegeneration with brain iron accumulation. These disorders can largely be distinguished from one another by their associated clinical and neuroimaging features. The aim of this study was to define the phenotype that is associated with mutations in WDR45, a new causative gene for neurodegeneration with brain iron accumulation located on the X chromosome. The study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
279
2
11

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 214 publications
(314 citation statements)
references
References 17 publications
(21 reference statements)
8
279
2
11
Order By: Relevance
“…It has been hypothesized that the gender bias was due to WDR45 variants lethality in males. 3 Along the same line, somatic mosaicism would explain the similar phenotype between the few affected males and female patients. Indeed, Haack et al 2 have confirmed the presence of somatic mosaicism in a male patient.…”
Section: Male Eoee With Wdr45 Deletionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been hypothesized that the gender bias was due to WDR45 variants lethality in males. 3 Along the same line, somatic mosaicism would explain the similar phenotype between the few affected males and female patients. Indeed, Haack et al 2 have confirmed the presence of somatic mosaicism in a male patient.…”
Section: Male Eoee With Wdr45 Deletionmentioning
confidence: 99%
“…2 WDR45 variants associated with BPAN syndrome have been almost exclusively found in females and only three male cases have been described to date. 3 This low incidence of male cases has been attributed to male lethality and the existence of a few male carriers to somatic mosaicism. 2 Among published cases, 70% of patients suffered from epileptic seizures beginning after 3 months of age.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unclear, however, whether hemizygous mutations in male patients are lethal. Hayflick's group reported three male SENDA patients with similar phenotypes [12,26]; all three may have had somatic mosaicism. These studies provided the first direct evidence that the deficiency of a core autophagy factor is indeed a contributing factor to human neurodegenerative diseases.…”
Section: Static Encephalopathy Of Childhood With Neurodegeneration Inmentioning
confidence: 99%
“…Besides PKAN caused by mutations in the PANK2 gene, [1,2] the best characterized subtypes include MPAN with mutations/deletions in the c19orf12 gene, [7][8][9] the PLA2G6 Associated Neurodegeneration (PLAN) with mutations in the PLA2G6 gene, [10] the Coasy Protein Associated Neurodegeneration (CoPAN) with mutations in the Coasy gene, [11] and the Beta-Propeller Protein Associated Neurodegeneration (BPAN) with mutations in the WDR45 gene. [12] A shared feature of these diseases is brain iron accumulation that is likely secondary to abnormalities in lipid metabolism and autophagy. [3,4] Figure 2.…”
Section: Resultsmentioning
confidence: 99%